Molecular and pharmacological modulators of the tumor immune contexture revealed by deconvolution of RNA-seq data - Finotello, Francesca; Mayer, Clemens; Charoentong, Pornpimol (Genome medicine, 2019)
We introduce quanTIseq, a method to quantify the fractions of ten immune cell types from bulk RNA-sequencing data. quanTIseq was extensively validated in blood and tumor samples using simulated, flow cytometry, and immunohistochemistry data.
Gesehen am 22.07.2019